Associations between neurocognitive functioning and social and occupational resilience among South African women exposed to childhood trauma. Issue 1 (1st January 2017) - Denckla, C. A.; Consedine, N. S.; Spies, G.; Cherner, M.; Henderson, D. C.; Koenen, K. C.; Seedat, S.
ABSTRACT: Background : Prior research on adaptation after early trauma among black South African women typically assessed resilience in ways that lacked contextual specificity. In addition, the neurocognitive correlates of social and occupational resilience have not been investigated. Objective : The primary aim of this exploratory study was to identify domains of neurocognitive functioning associated with social and occupational resilience, defined as functioning at a level beyond what would be expected given exposure to childhood trauma. Methods : A sample of black South African women, N = 314, completed a neuropsychological battery, a questionnaire assessing exposure to childhood trauma, and self-report measures of functional status. We generated indices of social and occupational resilience by regressing childhood trauma exposure on social and occupational functioning, saving the residuals as indices of social and occupational functioning beyond what would be expected given exposure to childhood trauma. Results : Women with lower non-verbal memory evidenced greater social and occupational resilience above and beyond the effects attributable to age, education, HIV status, and depressive and posttraumatic stress symptoms. In addition, women with greater occupational resilience exhibited lower semantic language fluency and processing speed. Conclusion : Results are somewhat consistent with prior studies implicating memory effects in impairment following trauma, though our findings suggest that reduced abilities in these domains may be associated with greater resilience. Studies that use prospective designs and objective assessment of functional status are needed to determine whether non-verbal memory, semantic fluency, and processing speed are implicated in the neural circuitry of post-traumatic exposure resilience.